Bridging the gap in 1 st year dental material curriculum: A 3 year randomized cross over trial - Sivaranjani Gali; Vibha Shetty; N S Murthy; P Marimuthu (Wolters Kluwer Medknow Publications, 2015)
Background: Case-oriented small group discussions (COSGDs) can help students to correlate and integrate the basic science of dental materials into clinical application. We used COSGDs along with didactic lectures in dental material curriculum and hypothesized that case-oriented group discussions would be more effective than traditional lecture alone in terms of performance of students, student perception on the above two teaching methodologies and the feasibility in classes of 2010, 2011 and 2012. Methods: A total of 170 students were taught using both COSGD and didactic lecture in a randomized controlled crossover trial design. Their performance was assessed through multiple-choice questions (MCQs) as part of the formative assessment, and their perception was assessed through Likert scale questionnaire. Results: The mean difference in the scores between case-oriented group discussions with lecture and didactic lecture showed significant difference only in few topics. Around 94-96% of students perceived COSGD with didactic lecture help them understand theory better; 76-92% of students feel more comfortable asking questions in a group discussion; 89-98% of students feel such discussions motivate them and 91-100% of students agree that discussions make the subject interesting in the respective years of 2010, 2011 and 2012. Conclusion: Effectiveness of COSGD in terms of scores through MCQs is comparable to traditional lecture. However, most of the students perceive COSGD help them understand the theory better; co-relate clinically; more motivating and interesting than a traditional lecture. Feasibility in institution needs more time and resources to conduct COSGD within the dental material curriculum.